2000
DOI: 10.1074/jbc.275.8.5633
|View full text |Cite
|
Sign up to set email alerts
|

Phenylethylthiazolylthiourea (PETT) Non-nucleoside Inhibitors of HIV-1 and HIV-2 Reverse Transcriptases

Abstract: A series of biaryl acids has been reported that inhibit both HIV-1 and HIV-2 RT, although these appear not to bind at the NNRTI site (4). NNRTIs such as nevirapine generally act as noncompetitive inhibitors of HIV-1 RT with respect to substrates (5), binding in a pocket some 10 Å from the polymerase active site (6 -8). The NNRTI binding site is contained largely within the p66 subunit of the RT heterodimer with only a few residues at the periphery of the site being contributed by the p51 subunit. The mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
125
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 41 publications
2
125
1
Order By: Relevance
“…Previous crystallographic studies have shown a common binding site for many classes of NNRTI, with a high degree of overlap for chemically divergent compounds (11)(12)(13)(14)(15)(16)(17)(18). Crystallographic and kinetic studies indicate the mechanism of inhibition of NNRTIs is via a distortion of the catalytic aspartate residues in the polymerase active site (19,20).…”
mentioning
confidence: 99%
“…Previous crystallographic studies have shown a common binding site for many classes of NNRTI, with a high degree of overlap for chemically divergent compounds (11)(12)(13)(14)(15)(16)(17)(18). Crystallographic and kinetic studies indicate the mechanism of inhibition of NNRTIs is via a distortion of the catalytic aspartate residues in the polymerase active site (19,20).…”
mentioning
confidence: 99%
“…Subsequent structures of the enzyme with a number of different NNRTIs bound have demonstrated that these inhibitors bind to the same pocket, with only minor differences in protein conformation, and substantially overlap the site occupied by nevirapine (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Comparison of these structures with those of the apoenzyme shows that the NNRTI-binding pocket is induced upon NNRTI binding (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Thiourea derivatives have been identified as Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTIs) [1][2][3][4][5]. There is an increasing concern on thioureas as someo ft hem also have been reported as antiviral [6][7][8], antibacterial [9] and anti-HIV agents [10].W ith the aim of obtaining new antibacterial compounds, (E)-(2-((2,3-dihydrobenzo[b] [1,4]dioxin-6-yl)methylene)-Nphenylhydrazinecarbothioamide was synthesized to study its crystal structure.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing concern on thioureas as someo ft hem also have been reported as antiviral [6][7][8], antibacterial [9] and anti-HIV agents [10].W ith the aim of obtaining new antibacterial compounds, (E)-(2-((2,3-dihydrobenzo[b] [1,4]dioxin-6-yl)methylene)-Nphenylhydrazinecarbothioamide was synthesized to study its crystal structure. Two intermolecular N-H×××Sh ydrogen bond (N×××S1: 3.413(2) Å, N2-H2×××S1: 151°) and an intramolecular N-H×××Nh ydrogen bond (N1×××N3: 2.595(3) Å, N1-H1×××N3: 110°) form in the molecule.Intotal, all bond lengths in the molecules are withinnormalvalues [11].…”
Section: Discussionmentioning
confidence: 99%